EFFECT OF NITRATE AND PHOSPATE CONCENTRATION ON Spirulina platensis WITH INDOOR SCALE - Mutia, Safira; Nedi, Syahril; Elizal, Elizal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2021)
One of the microalgae that are widely used in the industrial world is Spirulina platensis which has high nutritional content of protein, fatty acids, vitamins and antioxidants. In its growth, this microalgae requires media and the addition of macronutrients nitrate and phosphate which greatly affect the growth and productivity of S. platensis biomass. This study aims to determine the effect of nitrate and phosphate concentrations on S. platensis biomass on an indoor scale and to determine the optimal nitrate and phosphate concentrations to achieve maximum biomass. This research was conducted in August 2020 as an experimental method, with culturing S. platensis with the addition of different concentrations of nitrate and phosphate. The design used in this study was a Completely Randomized Design consisting of 5 treatments that are 0 ppm, 10 ppm, 20 ppm, 30 ppm, and 40 ppm, each treatment with 3 repetitions. The source of nitrate and phosphate used is NPK. Water quality parameters during culture with temperatures ranging from 29-30oC, salinity 25-26 ppt, and pH 8. The optimal concentrations of nitrate and phosphate to achieve the maximum biomass is in treatment C (30 ppm) with a total of biomass 0,43 g. Whereas in treatment D (40 ppm) the biomass did not show a significant increase because the dose was too high with a total of biomass only 0,299 g